The Impact of Environmental Policy on Foreign Trade: Tobey revisited with a Bilateral Flow Model - Cees van Beers; Jeroen C.J.M. van den Bergh (Tinbergen Institute, 2000)
We consider the microfoundations controversy from the perspective of economic evolution. Although the analogy between biology and economics has been noted before, it has rarely focused on clarifying the micro–macro distinction in economic theory and modelling. The micro–macro debate is more developed in biology than in economics owing to a greater degree of specialisation and a greater degree of interaction between various sub-disciplines. The task for economists is to distinguish between insights directly relevant for economic theory and ones that hinge on unique features of biological systems. We argue that both micro and macro processes drive economic change and that macroeconomic change cannot be explained by microlevel optimising alone. We show that debates in biology about group selection and punctuated equilibria are relevant to understanding economic evolution. The opposition of reductionism and holism is of little use and, in its place, a hierarchical approach is proposed. This allows for both upward and downward causation and interaction between levels.
Keywords: 330; Evolutionary biology; Group selection; Hierarchical causation; Punctuated equilibrium Sorting; Umweltpolitik; Internationale Wirtschaft; OECD-Staaten